Expanding TAVI to Low and Intermediate Risk Patients - Voigtländer, Lisa; Seiffert, Moritz (Frontiers in Cardiovascular Medicine, 2018)
TAVI has become the standard treatment in patients at increased surgical risk and is increasingly being performed in patients at intermediate to low surgical risk. While non-inferiority has been demonstrated in intermediate risk patients, several challenges – particularly with regard to valve durability – need to be addressed before expansion to lower risk and younger patients can be recommended on a broad basis. Current trends, trials results, and remaining challenges are summarized and discussed in the light of updated treatment guidelines.